Fever as an initial manifestation of spondyloarthritis: A retrospective study. - Se Jin Byun; William Han Bae; Seung Min Jung; Sang-Won Lee; Yong-Beom Park; Jason Jungsik Song (PLoS ONE)
Objectives We aimed to evaluate a wide spectrum of clinical features of adult patients with spondyloarthritis (SpA) whose initial manifestation was fever, using the Assessment of SpondyloArthritis international Society (ASAS) classification criteria. Methods We retrospectively collected the electronic medical records of hospitalized SpA patients who initially presented to the Severance Hospital (Seoul, Korea) with fever from January 2010 to May 2016. As a control group, we also recruited one-hundred consecutive patients who were diagnosed with SpA in our outpatient clinic. Clinical features and laboratory findings were compared in two patient groups. Results There were 26 patients who had fever as initial presentation of SpA (reactive arthritis 50%, undifferentiated SpA 26.9%, ankylosing spondylitis 15.4%, enteropathic arthritis 3.8%, psoriatic arthritis 3.8%). Peripheral SpA was more common in febrile SpA patients than in control SpA patients (65.4% vs 24.0%, p<0.001). Febrile SpA patients were less frequently HLA-B27 positive than control SpA patients (52.2% vs 77.0%, p<0.05). At baseline, systemic inflammatory markers were significantly higher in the febrile SpA patients (white blood cell count, 11.57 vs 7.81 cells/μL, p<0.001; erythrocyte sedimentation rate, 69.2 vs 41.0 mm/h, p<0.001; C-reactive protein, 109.6 vs 15.3 mg/L, p<0.001). The proportion of patients treated with systemic steroids was significantly higher in febrile SpA patients (57.7% vs. 11.0%, p<0.001). The proportion of patients who visited rheumatology specialty was significantly lower in febrile SpA patients than in control SpA patients (7.7% vs 59.0%, p<0.001). Conclusion Various subgroups of SpA can be presented with fever as an initial manifestation. Febrile SpA patients demonstrated higher systemic inflammation and a lower chance to visit rheumatology in early stage. When evaluating febrile patients with any clinical features of SpA, clinicians are advised to consider performing SpA-focused evaluation including HLA-B27 or a simple sacroiliac joint radiograph.